Pengembangan Masyarakat melalui Pendidikan Kajian Kitab Kuning: Studi Kitab Al-Iqtishod Al- Islami, Al Fiqh Al Islami Wa Adillatuhu, Tafsir Al- Qur'an, dan Ilmu Faraid dalam Program Friday Literacy - Rachmad, Dedy; Mustafa, Muhammad Isa; Afifi, Ahmad Levi Fachrul; Effendi, Erus (Tamkin Jurnal Pemberdayaan Tazkia, 2025)
Community service is a concept and practice in which individuals, groups, or institutions provide sustained positive contributions to society. The main goal of this service is to improve the quality of life for communities, address social issues, and support sustainable development. One tangible form of this service is through educational development via the Friday Literacy program. “Kitab kuning" refers to classical Islamic literature that encompasses various aspects of religion, such as religious knowledge, fiqh (Islamic law), tafsir (interpretation of the Qur'an), hadith (traditions of Prophet Muhammad), aqidah (belief), and others. The Friday Literacy program for the 2023/2024 period focuses its study on "Al-Iqtishod Al-Islami Li Al-Qur'an Al-Kariim" by Rafiq Yunus al-Mishriy, "Al Fiqh Al Islami Wa Adillatuhu" by Wahbah al- Zuhaili, and the understanding of Ilmu Faraid by Utsaimin. Ilmu Faraid is a monumental work in Islamic literature that discusses various aspects of the distribution of Islamic inheritance. Through the study of these works, it is hoped that Muslim communities can gain a deeper understanding of Islamic teachings, strengthen faith, and improve religious practices. Additionally, this study aims to support community empowerment and sustainable socio- economic development. The Friday Literacy program aims to enhance public understanding of "kitab kuning" and its contribution to socio-economic empowerment, serving as a reference for future program implementations and providing recommendations for further development in the field of Islamic education.